Role of Neoadjuvant Therapy in Management of Pancreatic Cancer - Li, Jia; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Surgery remains the only curative treatment for pancreatic cancer; however, majority of patients present with advanced unresectable disease upon diagnosis. Treatment of nonmetastatic, locally advanced pancreatic cancer (LAPC) continues to require multidisciplinary bimodality or trimodality approach. Neoadjuvant therapies have been investigated for LAPC given its established role in other solid cancers such as breast cancer, gastric cancer, and rectal cancer. This strategy is now moving forward to management of potentially resectable disease as well. This meeting highlight focuses on recent updates on neoadjuvant therapy for both borderline resectable disease and potentially resectable disease, Abstracts #4120, #e15189, #e15226 and #TPS4158 will be discussed. Image: Yale Cancer Center. New Haven, CT, USA.